Digital Innovation Strategy to Foster Customer Satisfaction Growth at Pegadaian Syariah: Strategi Inovasi Digital untuk Meningkatkan Kepuasan Pelanggan di Pegadaian Syariah - Nasution, M.Fuad Munawirsyah; Aslami, Nuri; Kusmilawaty (Indonesian Journal of Innovation Studies, 2025)
General Background: In the digital era, financial institutions face increasing competition, prompting the need for service innovation. Specific Background: Pegadaian Syariah AR Hakim has adopted digital strategies to enhance service efficiency and customer engagement. Knowledge Gap: However, the extent to which digital innovation impacts customer satisfaction in sharia-based pawnshops remains underexplored. Aims: This study aims to analyze strategies to improve customer satisfaction through digital innovation at Pegadaian Syariah AR Hakim. Results: Using qualitative methods and SWOT analysis, the study identifies 20 alternative strategies derived from internal and external factor assessments, including SO, WO, ST, and WT strategies. Novelty: The study offers a comprehensive application of SWOT in a sharia financial context, integrating customer interviews, digital literacy initiatives, and personalized services. Implications: The findings highlight the importance of balancing digital service development with customer education and technical reliability. These insights can guide similar institutions in formulating adaptive digital strategies aligned with customer expectations and regulatory frameworks.Highlight : Pegadaian Syariah AR Hakim uses digital innovation strategies (via mobile apps, data-driven personalization, etc.) to increase customer satisfaction. A SWOT analysis identified 20 strategic alternatives to address strengths, weaknesses, opportunities, and threats. The organization is in a growth-aggressive strategic position (Quadrant I), enabling it to pursue expansion and service development aggressively. Keywords : Customer Satisfaction, Digital Innovation, SWOT Analysis, Sharia Pawnshop, Pegadaian Syariah